The Effect of Heat Treatment on The Magnetic Properties of The (Fe-Mn) Alloys Prepared by Powder Metallurgy Method - I.K. Jassim; A.S. Msghen; A.S. Mahmood (Tikrit Journal of Pure Science, 2023)
This research studied the magnetic series of  (Fe1-xMnx)  which included the preparation alloys with weight ratios  (X=25,50,70,80)   by using Powder technology method . This study aimed to determine the Magnetic properties through the magnetic hestress loop . Number of magnetic properties  have been found such as Remained force (Br), Coerecive force (Hc),  Magnetic Relative permeability (µr) , and Magnetic Susceptibility (χm) for all study Samples . This experimental results were found a ferromagnetic behavior and sensitive to the heat treatment , which shows rapidity changeable to the paramagnetic behavior with the increasing the temperature degrees . The suitable heat treatment degree determined to get magnetic properties through the magnetic manufacturing operations . The results were explained due to the motion relation of magnetic spins with temperature degrees of heat treatment.